COMPARISON OF DEXMEDETOMIDINE 0.5MCG/KG IV OR 1MCG/KG IV WITH SALINE AS CONTROL FOR MONITORED ANAESTHESIA CARE IN POSTERIOR SEGMENT OPHTHALMIC SURGERY. A RANDOMIZED CONTROLLED TRIAL - Dr. Akshay Vijay sable; Dr. Shubhada Rajendra Deshmukh; Dr. Shweta Akash Patel (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Conscious sedation is often required during ophthalmic surgeries to ensure patient comfort and cooperation. Dexmedetomidine, an alpha-2 adrenergic agonist, has gained attention for its sedative and analgesic properties. This study investigates the effectiveness and safety of two doses of dexmedetomidine (0.5 µg/kg and 1 µg/kg) compared to a saline placebo in providing sedation for posterior segment ophthalmic surgeries.Methodology: A double-blind, block-randomized controlled trial was conducted on 75 patients undergoing posterior segment ophthalmic surgeries under local anesthesia. Participants were randomly assigned into three groups (n=25 each) to receive either dexmedetomidine 0.5 μg/kg (Group DL), 1 μg/kg (Group DH), or placebo (Group C) infused over 10 minutes. Sedation, analgesic requirements, hemodynamic parameters, and recovery profiles were assessed. Data were analyzed using STATA 10.1, with ANOVA, Chi-square test, and Games-Howell post hoc analysis applied; p